Pregnancy outcomes of prenatally diagnosed Turner syndrome: a French multicenter retrospective study including a series of 975 cases. (22nd July 2014) - Gruchy, N.; Vialard, F.; Blondeel, E.; Le Meur, N.; Joly‐Hélas, G.; Chambon, P.; Till, M.; Herbaut‐Graux, M.; Vigouroux‐Castera, A.; Coussement, A.; Lespinasse, J.; Amblard, F.; et al.
ABSTRACT Objectives The objectives of this study were to report pregnancy outcomes after prenatal diagnosis of Turner syndrome (TS) and to compare and assess termination of pregnancy rates during two periods. The intervals selected were before and after 1997 when multidisciplinary centers for prenatal diagnosis (MCPDs) were established in France. Methods A database of 975 cases of TS diagnosed between 1980 and 2012 was created from 21 French cytogenetics laboratories. For each case, the karyotype indication, maternal age, year of prenatal testing, sampling procedure, karyotype, associated ultrasound findings, and outcomes were recorded. Results Karyotypes were mainly performed because of abnormal sonographic findings (84%). Before 1997, there were no changes in the rate of termination (90%) of affected fetuses. After 1997, the rate fell to 80%. This decrease was mainly observed in cases of mosaicism, incidental diagnosis, and in later gestations. US abnormalities were more likely to be associated with a full 45, X karyotype. Conclusion There was an evolution in the way genetic counseling was performed following prenatal diagnosis of Turner syndrome that coincided with the opening of MCPDs in France. This resulted in a decrease in the rate of termination of affected fetuses. © 2014 John Wiley & Sons, Ltd.